Halal awareness among non-muslims in gardenia bakeries (KL) sdn. bhd - Salim, Syamimi; Ibrahim, Nurshahira; Md Aris, Muhamad Azlan (GADING Journal for the Social Sciences, 2024)
This research delves into the significance of halal certification in Malaysia‟s food industry, particularly focusing on non-Muslim perspectives at Gardenia Bakeries (KL) Sdn. Bhd. Halal certification plays an important role in the food and beverage industry in Malaysia. It serves as a guarantee of religious compliance, safety, and hygiene for food products. The findings of this study provide insights into the level of halal awareness among non-Muslims and its impact on their acceptance of halal food. The results highlight the level of understanding and awareness among non-Muslims regarding halal practices. Therefore, the relevant authorities can develop a comprehensive halal awareness program to emphasize the importance of halal certification to consumers, regardless of their race or religion.